2002
DOI: 10.1128/jcm.40.9.3281-3285.2002
|View full text |Cite
|
Sign up to set email alerts
|

Mycobacterium microti Infection (Vole Tuberculosis) in Wild Rodent Populations

Abstract: Mycobacterium microti (vole tuberculosis) infections in small wild mammals were first described more than 60 years ago in several populations in Great Britain. Few studies of vole tuberculosis have been undertaken since then, and little is known about the relationship between M. microti isolates originating from different populations or at different times or of the prevalence of this infection in wild rodent populations, despite human cases of M. microti infections being increasingly reported. In this study, f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

3
89
2
2

Year Published

2004
2004
2019
2019

Publication Types

Select...
3
3
2

Relationship

0
8

Authors

Journals

citations
Cited by 87 publications
(96 citation statements)
references
References 19 publications
3
89
2
2
Order By: Relevance
“…Infected voles can live for as long as 52 weeks, and the author comments on how extensive tuberculosis can be without producing obvious symptoms. Although we cannot be certain that all the organisms described in the 1946 manuscript are M. microti, although some strains were shown to have distinctive M. microti spoligotype patterns and deletion profiles in later studies (1,5,25), the distinctive cellular morphology when viewed microscopically supports this identification. The author mentions that growth is very slow and variable upon primary isolation and is substantially faster after repeated subculture and also reports on a number of studies using live strains of the vole bacillus as a vaccine in guinea pigs, cattle, and humans and suggests that the vole bacillus does not cause progressive disease in these animals unless given in large doses (43).…”
mentioning
confidence: 72%
See 2 more Smart Citations
“…Infected voles can live for as long as 52 weeks, and the author comments on how extensive tuberculosis can be without producing obvious symptoms. Although we cannot be certain that all the organisms described in the 1946 manuscript are M. microti, although some strains were shown to have distinctive M. microti spoligotype patterns and deletion profiles in later studies (1,5,25), the distinctive cellular morphology when viewed microscopically supports this identification. The author mentions that growth is very slow and variable upon primary isolation and is substantially faster after repeated subculture and also reports on a number of studies using live strains of the vole bacillus as a vaccine in guinea pigs, cattle, and humans and suggests that the vole bacillus does not cause progressive disease in these animals unless given in large doses (43).…”
mentioning
confidence: 72%
“…We therefore suggest that cats and the mammals other than voles listed in Table 1 are acting as a spillover host for disease present in a wildlife maintenance host; the geographical localization of M. microti genotypes would be preserved by the distribution of infection in the wildlife maintenance host. The most likely maintenance host for M. microti in Great Britain is the field vole (Microtus agrestis), which has been reported as having a high prevalence of the disease in several studies (3,5,6,43).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Numerous pathogens associated with rodents are not included in the IUCN guidelines; for example, E. multilocularis has been reported in Eurasian beavers in Switzerland (Janovski et al, 2002), but not on mainland Norway, and in one captive beaver in the United Kingdom (Barlow et al, 2011). Mycobacterium microti (Cavanagh et al, 2002), cowpox virus (Carslake et al, 2005), Cryptosporidium parvum (Quy et al, 1999), Eimeria spp. (Lewis and Ball, 1983), Bartonella (Birtles et al, 2001), Toxoplasma (Hay et al, 1983), and Leptospira (Salt and Little, 1977) have all been reported in UK wild rodent populations, and thus released beavers may become exposed.…”
Section: Discussionmentioning
confidence: 99%
“…This species was originally described as the cause of tuberculosis (TB) in wild rodents. Indeed, field voles (Microtus agrestis), bank voles (Myodes glareolus), wood mice (Apodemus sylvaticus), and shrews (Sorex araneus), which are particularly susceptible to M. microti infection, constitute its natural reservoirs (1). However, an increasing number of cases have also been reported in domestic and wild mammals (2), such as cats (3,4), pigs (5), European wild boar (Sus scrofa) (6), ferrets (Mustela putorius), badgers (Meles meles) (4), New World camelids (Lama glama and Vicugna pacos) (4), squirrel monkeys (Saimiri sciureus) (7), meerkats (Suricata suricatta) (8), and a dog (9).…”
mentioning
confidence: 99%